Inhaled Hydrogen Sulfide Improves Graft Function in an Experimental Model of Lung Transplantation - George, Timothy J. (2012)
OBJECTIVES: Ischemia-reperfusion(IRI) is a common complication of lung transplantation(LTx). Hydrogen sulfide(H(2)S) is a novel agent previously shown to slow metabolism and scavenge reactive oxygen species, potentially mitigating IRI. We hypothesized that pre-treatment with inhaled H(2)S would improve graft function in an ex vivo model of LTx. METHODS: Rabbits(n=10) were ventilated for 2 hours prior to heart-lung bloc procurement. The treatment group(n=5) inhaled room air(21% O(2)) supplemented with 150 ppm H(2)S while the control group(n=5) inhaled room air alone. Both groups were gradually cooled to 34 C. All heart-lung blocs were then recovered and cold-stored in low potassium dextran solution for 18 hours. Following storage, the blocs were reperfused with donor rabbit blood in an ex vivo apparatus. Serial clinical parameters were assessed and serial tissue biochemistry was examined. RESULTS: Prior to heart-lung bloc procurement, rabbits pre-treated with H(2)S exhibited similar oxygenation(p=0.1), ventilation(p=0.7), and heart rate(p=0.5); however, treated rabbits exhibited consistently higher mean arterial blood pressures(p=0.01). During reperfusion, lungs pre-treated with H(2)S had better oxygenation(p<0.01) and ventilation(p=0.02) as well as lower pulmonary artery pressures(p<0.01). Reactive oxygen species levels were lower in treated lungs during reperfusion(p=0.01). Additionally, prior to reperfusion, treated lungs demonstrated more preserved mitochondrial cytochrome c oxidase activity(p=0.01). CONCLUSIONS: To our knowledge, this study represents the first reported therapeutic use of inhaled H(2)S in an experimental model of LTx. After prolonged ischemia, lungs pre-treated with inhaled H(2)S exhibited improved graft function during reperfusion. Donor pre-treatment with inhaled H(2)S represents a potentially novel adjunct to conventional preservation techniques and merits further exploration.